Konsep Tuhan Dalam Tradisi Barat Serta Kritik Terhadap Pandangan Tentang Tuhan Personal Dan Non-Personal - Gede Agus Siswadi (Tampung Penyang, 2024)
Humans are creatures who never stop searching, various things that humans want to uncover, because humans have a uniqueness that always questions various things around them, including about God. Thus, there are various views on the concept of God. This research explores the concept of God in the Western tradition with a focus on the views of personal and non-personal God. The main objective of this research is to understand how these concepts have developed in the history of Western thought. The research method in this study is a qualitative method with a hermeneutic approach as well as literature analysis. The results show that various concepts of God are understood in Western society, such as God as a person, God the Eternal, God the Immanent and Transcendent, God is Most Kind, God the Almighty, God the Creator and so on. Then, criticism of the concept of personal God emphasises the potential for anthropomorphism, the difficulty of explaining the existence of evil and suffering, and the question of human freedom in the context of divine will. Meanwhile, criticism of the non-personal God concept highlights the potential lack of personal closeness, abstraction that is difficult to understand, and the potential lack of human moral responsibility.